Lanthanum strontium vanadate in solid oxide fuel cells. - Ge, Xiaoming. (2012)
Solid oxide fuel cells (SOFCs) are high temperature energy conversion devices with the advantages of fuel flexibility and high efficiency. Limitations of SOFC cermet anodes have been stimulating oxide anodes. Lanthanum strontium vanadate, La1-xSrxVO3 (LSV, 0 ≤ x ≤ 1), have been synthesized and examined as potential SOFC anode materials. LSV appear to be chemically compatible with yttria-stabilized zirconia (YSZ) at least up to 1300°C. Electrode performance is evaluated by impedance spectroscopy and dc polarization between 800 to 1000°C. Good electrode performance is achieved with LSV(x = 0.2, 0.3, 0.4, 0.5)–YSZ composite anodes, in both pure H2 and 3% H2O humidified CH4. For half-cells with La0.6Sr0.4VO3–YSZ anode, polarization resistance is 0.85 Ω cm2 and 1.38 Ω cm2 at 900°C in pure H2 and wet CH4, respectively. When drawing a current of 0.2 A/cm2 at 900°C, the overpotential is 0.13 V in pure H2, and slightly higher in wet CH4, 0.20 V. Further optimization of electrode microstructures is needed to maximize the performance of LSV for potential SOFC application.